The exonuclease Nibbler regulates age-associated traits and modulates piRNA length in Drosophila. - Feltzin, V.L.; Khaladkar, M.; Abe, M.; Parisi, M.; Hendriks, G.J.; Kim, J.; Bonini, N.M. (Aging Cell, 2015)
Nibbler (Nbr) is a 3'-to-5' exonuclease that trims the 3'end of microRNAs (miRNAs) to generate different length patterns of miRNAs in Drosophila. Despite its effect on miRNAs, we lack knowledge of its biological significance and whether Nbr affects other classes of small RNAs such as piRNAs and endo-siRNAs. Here, we characterized the in vivo function of nbr by defining the Nbr protein expression pattern and loss-of-function effects. Nbr protein is enriched in the ovary and head. Analysis of nbr null animals reveals adult-stage defects that progress with age, including held-up wings, decreased locomotion, and brain vacuoles, indicative of accelerated age-associated processes upon nbr loss. Importantly, these effects depend on catalytic residues in the Nbr exonuclease domain, indicating that the catalytic activity is responsible for these effects. Given the impact of nbr on miRNAs, we also analyzed the effect of nbr on piRNA and endo-siRNA lengths by deep-sequence analysis of libraries from ovaries. As with miRNAs, nbr mutation led to longer length piRNAs - an effect that was dependent on the catalytic residues of the exonuclease domain. These analyses indicate a role of nbr on age-associated processes and to modulate length of multiple classes of small RNAs including miRNAs and piRNAs in Drosophila.